Caffeic acid-grafted high-amylose maize starch for self-stabilizing emulsion gels: efficient encapsulation and protection of pterostilbene - Liling Fu; Yanan Ren; Conghe Zhang; Wei Yang; Guixiang Zhou; Tian Xu; Changhong Liu; Lei Zheng (Food Chemistry, 2026)

Antimony exposure promotes cardiac fibrosis via lactate-mediated cardiomyocyte-fibroblast crosstalk: A novel Sirt1-glycolysis axis - Xin Li; Zhenzhen Dai; Xiaoyong Ren; Hao Zhao; Lirong Chan; Ruotong Wu; Xinyi Xiao; Qiao Liu; Liling Su (Journal of Environmental Sciences, 2026)

A novel Pickering emulsion stabilized solely by n-butyric acid-modified high-amylose corn starch for resveratrol delivery - Liling Fu; Yanan Ren; Conghe Zhang; Wei Yang; Qisheng Tian; Guixiang Zhou; Tian Xu; Changhong Liu; Lei Zheng (Carbohydrate Polymers, 2026)

NLRC3 attenuates osteoclastogenesis by limiting TNFα+ Th17 cell response in osteoporosis - Lingyan Ren; Guangjun Liu; Yun Bai; Liling Gu; Yuan Wang; Li Sun (Journal of Molecular Medicine, 2024)
NOD-like receptor family CARD domain containing 3 (NLRC3) is the intracellular protein belonging to NLR (NOD-like receptor) family. NLRC3 can negatively regulate inflammatory signal transduction pathways within the adaptive and innate immunocytes. However, studies need to elucidate the biological role of NLRC3 in bone remodeling. Herein, our study proved that NLRC3 prevents bone loss by inhibiting TNFα + Th17 cell responses. In osteoporosis, NLRC3 attenuated TNFα + Th17 cell accumulation in the bone marrow. However, osteoporosis (OP) development was aggravated without affecting bone marrow macrophage (BMM) osteoclastogenesis in NLRC3-deficient ovariectomized (OVX) mice. In this study, we transferred the wild-type and NLRC3 −/− CD4 + cells into Rag1 −/− mice. Consequently, we evidenced the effects of NLRC3 in CD4 + T cells on inhibiting the accumulation of TNFα + Th17 cells, thus restricting bone loss in the OVX mice. Simultaneously, NLRC3 −/− CD4 + T cells promoted the recruitment of osteoclast precursors and inflammatory monocytes into the OVX mouse bone marrow. Mechanism-wise, NLRC3 reduced the secretion of TNFα + Th17 cells of RANKL, MIP1α, and MCP1, depending on the T cells. In addition, NLRC3 negatively regulated the Th17 osteoclastogenesis promoting functions via limiting the NF-κB activation. Collectively, this study appreciated the effect of NLRC3 on modulating bone mass via adaptive immunity depending on CD4 + cells. According to findings of this study, NLRC3 may be the candidate anti-OP therapeutic target. Key messages NLRC3 negatively regulated the Th17 osteoclastogenesis promoting functions via limiting the NF-κB activation. NLRC3 may be the candidate anti-OP therapeutic target.

Synergistic effects of carbon cap-and-trade and renewable portfolio standards on renewable energy diffusion - Xiongping Yue; Chao Wang; Boxue Sun; Huanyu Ren; Yong Tan; Liling Huang; Dan Feng; Xin Li (Journal of Cleaner Production, 2023)

Prefabrication of axially vascularized bone by combining β-tricalciumphosphate, arteriovenous loop, and cell sheet technique - Dongyang Ma; Liling Ren; Zhen Cao; Jianxue Li; Jian Cao; Wenyan Tian; Hong Yao (Tissue Engineering and Regenerative Medicine, 2016)